Effect of austempering temperature and manganese content on the impact energy of austempered ductile iron. Issue 1 (1st January 2021) - Hegde, Ananda; B M, Gurumurthy; Hindi, Jamaluddin; Sharma, Sathyashankara; M C, Gowrishankar
Abstract: Austempered ductile iron (ADI) is a revolutionary material that has the ability to replace some of the commonly used steel forgings. ADI is being used in wide range of products because of the availability of this material with relatively lesser cost and its higher strength to weight ratio. Manganese is an important alloying element added to ductile iron for improving the hardenability. However, the amount of manganese has to be carefully selected to avoid any adverse effect on the mechanical properties. In this study, impact energy and tensile properties are determined for the various austempering temperatures and manganese content. Statistical analysis is carried out to determine the relative contribution of each factors on the results. Higher impact energy is observed at the higher austempering temperature of 420°C. No adverse effect on impact energy is observed for the addition manganese up to 1 wt%. Response surface methodology is used to optimize the parameters for obtaining the superior combination of ultimate tensile strength and impact energy. Regression equations are fit to predict the impact energy and ductility of manganese alloyed ADI.